Critical forensic studies - Julian, Roberta; Howes, Loene; White, Rob (Professor of criminology) (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book provides a comprehensive overview of the emerging interdisciplinary field of 'critical forensic studies'. It reviews existing research and scholarship on forensic science from a critical social science perspective, while forging a blueprint for further work in this area. Forensic science has long captured the public imagination, as evidenced by the popularity of novels, television programs, and true-crime podcasts. At the same time, its role in the criminal justice system has been the subject of critique from scholars and practitioners in diverse fields. In response, the international forensic science community has become more involved in the scrutiny of its own knowledge and practices in relation to criminal justice objectives. Moving beyond a discussion of forensic science as a suite of specialised scientific disciplines that aim to provide evidence to the courts, Critical Forensic Studies offers critical insights relevant to a wide range of social actors in the criminal justice system. Core content includes: History and public understandings of forensic science; The professionalisation of forensic science; Forensic science as a social process; Crime scene examination and forensic intelligence; Experts and evidence in court; Technological advances and human rights; Interdisciplinary knowledge, practice and research. This book is essential reading for forensic and criminal justice practitioners and students across criminology, sociology, forensic science, law, and psychology"--
Keywords: Forensic sciences; Crime scene searches; Criminology; Criminal justice, Administration of; LAW / Forensic Science; SOCIAL SCIENCE / Criminology